Carbon quantum dot micelles tailored hollow carbon anode for fast potassium and sodium storage. (November 2019) - Hong, Wanwan; Zhang, Yu; Yang, Li; Tian, Ye; Ge, Peng; Hu, Jiugang; Wei, Weifeng; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Carbonaceous materials are promising anode materials for alkali-metal ion batteries due to the abundant resource and high safety, while it is challenged by its low specific capacity and depressed rate capability in potassium-ion batteries (PIBs). To further explore the potassium storage properties of carbon materials and exploit high-performance carbon anode for PIBs, in this work, hollow nanostructured N-doped carbon (p-HNCs) is elaborately designed through the tailoring of carbon quantum dots (CQDs) for the first time. The detailed formation mechanism of hollow nanostructure is investigated and it is demonstrated that CQD micelles formed through hydrophobicity and lipophilicity are served not only as templates for the construction of hollow structure but also pore-forming agent for the generation of rich micro-tunnels, due to the decomposition and contraction of CQDs with releasing gases during the pyrolysis process. When applied for potassium storage, p-HNCs anode delivers high reversible specific capacities of 254 mAh g-1 at 0.1 A g-1 after 100 cycles and 160 mAh g-1 at 1.0 A g-1 after 800 cycles. Notably, a desirable rate capability of 145 mAh g-1 is observed at 4.0 A g-1, derived from surface-driven behaviors. Moreover, galvanostatic intermittent titration technique measurement quantifies the improved diffusion coefficient of p-HNCs, indicating its superior kinetic property. This work shows us the special application of CQDs in structure construction and a valuable strategy to design high-performance carbon anode for potassium-ion batteries and sodium-ion batteries. Graphical abstract: Carbon quantum dot (CQD) micelles are applied for the first time to tailor the construction of hollow N-doped carbon, which is demonstrated for the enhanced performance of potassium storage. And splendid capacity of 160 mAh g −1 at 1.0 A g −1 after 800 cycles and desirable rate capability of 145 mAh g −1 are observed at 4.0 A g −1 . Image 1 Highlights: Hollow nanostructured N-doped carbon (p-HNCs) is designed. Carbon quantum dots are served as neoteric templates and pore-forming agents. Superb cyclic stability and rate capability are achieved for K-storage.